Yersinia enterocolitica arthritis in southern Sweden: a four-year follow-up study. Issue 6284 (11th July 1981) - Marsal, L; Winblad, S; Wollheim, F A
Abstract : Thirty-eight cases of suspected yersinia arthritis occurring in southern Sweden in 1975-6 were reviewed four to five years later. In 31 cases the diagnosis was confirmed. At follow-up three of the patients had definite ankylosing spondylitis, three radiologically confirmed sacroiliitis, three extensor tenosynovitis, five isolated articular joint disease, and 10 localised arthralgias; one patient had developed seropositive rheumatoid arthritis. Only six of the 31 patients were free of joint symptoms. These results suggest that although the acute symptoms of yersinia arthritis disappear within 12 months, the long-term prognosis may be less favourable than previously thought.